2011
DOI: 10.1038/modpathol.2011.77
|View full text |Cite
|
Sign up to set email alerts
|

The dichotomy in carcinogenesis of the distal esophagus and esophagogastric junction: intestinal-type vs cardiac-type mucosa-associated adenocarcinoma

Abstract: Adenocarcinoma of the distal esophagus and esophagogastric junction continues to rise in incidence. An intestinal metaplasia (Barrett esophagus)-dysplasia-carcinoma sequence induced by gastroesophageal reflux disease is well established. However, a significant number of adenocarcinomas in the vicinity of the esophagogastric junction are seen in the background of gastric/cardiac-type mucosa without intestinal metaplasia. Thus, the aim of this study was to investigate the role of Barrett esophagus (intestinal-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 59 publications
5
24
0
6
Order By: Relevance
“…Interestingly, SATB1 expression was significantly lower in primary tumors associated with IM than in primary tumors not associated with IM. This is in line with at least two different pathways of gastroesophageal carcinogenesis, one intestinal (arising from dysplasia in IM) and one non-intestinal (arising from cardia-type mucosa), the former being associated with better overall survival [32]. Our cohort showed a similar trend, which is in agreement with SATB1 expression as a negative prognostic factor.…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, SATB1 expression was significantly lower in primary tumors associated with IM than in primary tumors not associated with IM. This is in line with at least two different pathways of gastroesophageal carcinogenesis, one intestinal (arising from dysplasia in IM) and one non-intestinal (arising from cardia-type mucosa), the former being associated with better overall survival [32]. Our cohort showed a similar trend, which is in agreement with SATB1 expression as a negative prognostic factor.…”
Section: Discussionsupporting
confidence: 88%
“…Recognition of gastric foveolar and serrated dysplasia in BE may indicate the presence of distinct pathways of carcinogenesis in BE: an intestinal pathway that involves intestinal metaplasia versus a gastric pathway that involves foveolar dysplasia, but this theory has not been well-investigated [87][88]. In a recent study of 156 patients that underwent resection of BE associated adenocarcinoma, Agoston et al…”
Section: Accepted Manuscriptmentioning
confidence: 94%
“…94 Thus, some authorities have proposed that there are, at minimum, two distinct mechanisms of cancer development in BE, one with an intestinal precursor and one with a gastric epithelium precursor. 94–96 In a recent study of 156 patients that underwent resection of BE associated adenocarcinoma, Agoston et al found that 122 patients (78%) showed dysplasia in background mucosa and that, in general, the type of dysplasia (i.e. intestinal, foveolar or mixed) correlated with the type of adenocarcinoma that was present in the esophagus.…”
Section: Pathology Of Dysplasia In Barrett’s Esophagusmentioning
confidence: 99%